Bone marrow involvement in solid tumors - a retrospective observational study - Zhang, Bicheng; Jin, Lan; Wu, Dang; Xu, Jing; Guo, Siyu; Li, Jingjing; Zhang, Ting (Frontiers in Oncology, 2025)
BackgroundSolid tumor patients with bone marrow involvement (BMI) typically have a poor prognosis. However, some patients still exhibit a relatively good prognosis following aggressive treatment. This study aimed to identify prognostic factors to stratify patients and screen those who may benefit from aggressive treatment.MethodsA total of 41 consecutive patients diagnosed with a bone marrow biopsy were enrolled between January 1, 2016, and December 31, 2021. Then, their clinical features and laboratory data were assessed using the Chi-square test. Overall survival (OS) rates were plotted over time using the Kaplan-Meier method. Lastly, the survival time of solid tumor patients with BMI with distinct clinical symptoms, peripheral hematologic profiles, biochemical profiles, and coagulation function were analyzed using the Kaplan-Meier method.ResultsThe median OS of the whole cohort was 23 days. Specifically, the median OS of patients (n = 40) receiving anti-tumor treatment (n = 12) and supportive care (n = 28) was 158 days and 13 days, respectively (P < 0.001). Interestingly, the prognosis of patients with BMI and normal leukocyte count, platelet count, glutamic-pyruvic transaminase (GPT) level, and plasma prothrombin time (PT), as well as lactate dehydrogenase (LDH) level less than twice the normal upper limit and alkaline phosphatase (AKP) less than five times the normal upper limit, was relatively favorable. Conversely, elevated levels of LDH, AKP, GPT, prolonged PT, abnormal leukocyte count, and thrombocytopenia were associated with a poor prognosis.ConclusionsSolid tumor patients with BMI can benefit from aggressive anti-tumor treatments. Additionally, early diagnosis of BMI in solid tumor patients, selection of patients with a potential good prognosis, and administering appropriate anti-tumor treatments are key factors in prolonging the survival time of BMI patients.